Pseudonyms in IPv6 ITS Communications: Use of Pseudonyms, Performance Degradation, and Optimal Pseudonym Change. (19th May 2015) - Lee, Jong-Hyouk; Lee, Giwon; Pack, Sangheon
Abstract : IPv6 developed as a next generation Internet protocol will provide us with safer and more efficient driving environments as well as convenient and infotainment features in cooperative intelligent transportation systems (ITS). In this paper, we introduce the use of pseudonyms in IPv6 ITS communications for preserving location privacy. We conduct qualitative study on the performance degradation due to the use of pseudonyms and quantitative analysis on the optimal pseudonym change interval. Numerical results demonstrate that an appropriate pseudonym change interval should be changed depending on the packet arrival rate, mobility rate, and security level.